Предмет: Математика,
автор: катька567904
решите уравнения: -x-2+3(x-3)=3(4-x)-3
Ответы
Автор ответа:
0
-х - 2 + 3(х - 3) = 3(4 - х) - 3
- х - 2 + 3х - 9 = 12 - 3х - 3
-х + 3х + 3х = 2 + 9 + 12 - 3
5х = 20
х = 4
- х - 2 + 3х - 9 = 12 - 3х - 3
-х + 3х + 3х = 2 + 9 + 12 - 3
5х = 20
х = 4
Автор ответа:
0
-х-2+3(х-3)=(4-х)-3
-х-2+х-9=8-2х-3
2х+2х=11+8-3
4х=16
х=16:4
х=4
-х-2+х-9=8-2х-3
2х+2х=11+8-3
4х=16
х=16:4
х=4
Похожие вопросы
Предмет: Психология,
автор: sakhapovajin
Предмет: Английский язык,
автор: hokizopa
Предмет: Українська мова,
автор: bakka1989
Предмет: Литература,
автор: Alice21345
Предмет: Математика,
автор: nikdemidov